Energy price slump and policy response in the coal-chemical industry district: A case study of Ordos with a system dynamics model. (May 2017) - Wang, Delu; Ma, Gang; Song, Xuefeng; Liu, Yun
Abstract: We employ system dynamics method towards a coal-chemical industry district economy evolution model, using coal industry, the coal-chemical industry, their downstream industries, and the manufacture-related service industry. Moreover, we construct energy price and policy response scenarios based on Ordos' management experience. The results show that the energy price slump had a negative impact on the overall economic development of the coal-chemical industry district, despite promoting non-resource industries. Furthermore, policies had different effects on the industry's output value and profit. In the long-term, developing alternative industries (AI) helps increase the industrial output value and profit. Decreasing value added tax (VAT) has immediate results and a distinctive effect on industrial short-term production value and profit, its long-term effect being limited. The effect of production limit (PL) on industrial profit is stronger than output value, and financial support (FS) is more conducive to improve the latter. However, coal mining and coal-chemical loan increases decrease the gross industrial profit level. Technology innovation (TI) has the best individual policy overall effect on production value and profits. Furthermore, the simultaneous implementation of PL, TI and AI can generate the synergy effect for each of them. And the simultaneous implementation of VAT and one or couple of other policies will generate the crowding-out effect both for VAT and other policies. Highlights: A system dynamics model of the coal-chemical industry district economy evolution in Ordos is constructed. The impact of coal and oil prices slump on the output value and profit of each industry is revealed. The differences in the effects especially cumulative effects of different response policies are clarified. The crowding-out and synergy effects of policy implementation are analyzed.